ANALISA BUDAYA KESELAMATAN PASIEN PADA IMPLEMENTASI PELAPORAN INSIDEN KESELAMATAN PASIEN DALAM UPAYA MENINGKATKAN MUTU PELAYANAN DI RAWAT INAP RUMAH SAKIT X - Wardhana, Bagus Kusuma; Aziz, Abdul; Subardi, Arda Yunita; Dwinuarisha, Eggie (Jurnal Penelitian Kesmasy, 2024)
The incident reporting system in Indonesia in 2019 found around 12% of 2877 hospitals reporting patient safety incidents, with the number of patient safety incident reports as many as 7465, the number consisting of Near Miss Incidents 38%, Non-Injury Incidents 31% and Adverse Events 31% (Daud, 2020). The aim is to analyze the implementation of patient safety incident reporting in inpatient care at Hospital X so that priority problems are found and alternative solutions are obtained. The design processes the data obtained using a qualitative approach through in-depth interviews, observations, and comparisons with ideal conditions based on the latest regulations. This activity was carried out during the period from May to July 2024. The results of the examination during the research process found several problems, namely there was a fear of reporting patient incidents, not being used to carrying out the reporting process and not understanding the categories of patient incidents, limited human resources in the safety culture quality team, having a sense of burden such as getting additional tasks if reporting patient incidents, the safety culture quality team has several other important tasks / is not focused, and the implementer feels that complaints related to the cause of the incident are not followed up. Based on the priority assessment using the Urgency, Seriousness and Growth method, the highest point was 24, which came from the problem of the implementer feeling that complaints related to the cause of the incident were not followed up or the implementer's misperception of the follow-up to reporting patient safety incidents. Hospital X should develop a patient safety incident reporting system (SIPENKES) by showing the incident reporting follow-up process on the front page of the information system so that it is more transparent and the implementer is expected to understand that there is feedback and remain enthusiastic about cultivating the reporting of patient safety incidents.